Cecília Meireles e a Índia: uma experiência de tradução - Ana Amélia Neubern Batista dos Reis (2015)
The present research intends to reveal an approach of Cecília Meireles' work that is scarcely studied: the author as a translator of the Indian writer Rabindranath Tagore. Besides reflecting about the effective translation of the novel Çaturanga, from Tagore, this study aims to deepen another rare studied aspect of Cecília Meireles' literary production, that is, the traces of Indian philosophy and culture constant in the Brazilian writer's work.